Meanings Of Particle Al-Lam Al-Jarrah: Analysing The Between Irtishaf Al-Darab Min Lisan Al'arab Differences And Mughni Al-labib 'An Kutub Al-a'arib - Wan Moharani Mohammad; Maheram Ahmadi ,; Hakim Zainal; Lubna Abd Rahman (Usuli Faqih Research Centre PLT, 2024)
Non-Indexed publication